Achieving Long Cycle Life of Zn-Ion Batteries through Three-Dimensional Copper Foam - Camurcu, Taskin; Demirbas, Erhan; Ates, Mehmet Nurullah (Amer Chemical Soc, 2024)
Metallic zinc anodes in aqueous zinc-ion batteries (ZIBs) suffer from dendritic growth, low Coulombic efficiency, and high polarization during cycling. To mitigate these challenges, current collectors based on three-dimensional (3D) commercial copper foam (CCuF) are generally preferred. However, their utilization is constrained by their thickness, low electroactive surface area, and increased manufacturing expenses. In this study, the synthesis of cost-effective current collectors with exceptionally large surface areas designed for ZIBs that can be cycled hundreds of times is reported. A zinc-coated CuF anode (Zn/CuF) was prepared with a 3D porous CuF current collector produced by the dynamic hydrogen bubble template (DHBT) method. Electrochemically generated copper foam could be obtained within seconds while offering a thickness as low as 30-40 mu m (CuF5 achieved a thickness of similar to 38 mu m in 5 s) via the DHBT method. The excellent electrical conductivity and open pore structure of the 3D porous copper scaffold ensured the uniform deposition/stripping of Zn during cycling. During the 500 h Zn deposition/stripping process, the as-synthesized CuF5 current collector offered fast electrochemical kinetics and low polarization as well as a relatively high average Coulombic efficiency of 99% (at a current density of 5 mA cm-2 and a capacity of 1 mAh cm-2). Furthermore, the symmetric cell exhibited low voltage polarization and a stable voltage profile for 1000 h at a current density of 0.1 mA cm-2. In addition, full cells containing the Zn/CuF anode coupled with an as-synthesized alpha-MnO2 nanoneedle cathode in aqueous electrolyte were also prepared. Capacities of 266 mAh g-1 at 0.1 A g-1 and 94 mAh g-1 at 2 A g-1 were achieved after 200 charge/discharge cycles with a stable Coulombic efficiency value close to 99.9%.
Keywords: aqueous batteries; zinc-ion batteries; 3D copperfoam; thin foam; current collectors